Inside Back Cover: Docking of CuI and AgI in Metal–Organic Frameworks for Adsorption and Separation of Xenon (Angew. Chem. Int. Ed. 7/2021). Issue 7 (4th January 2021) - Wang, Haoze; Shi, Zhaolin; Yang, Jingjing; Sun, Tu; Rungtaweevoranit, Bunyarat; Lyu, Hao; Zhang, Yue‐Biao; Yaghi, Omar M.
Abstract : Xenon separation   from krypton by porous adsorbents is a sustainable technology for the production of small‐volume but high‐value noble gases. MOFs are designer xenon adsorbents whose adsorption separation performance can be enhanced by tuning the pore metrics, functionalities, and counterions. In their Communication on page 3417, Yue‐Biao Zhang, Omar M. Yaghi, and co‐workers describe a new methodology for postsynthetic metalation of MOFs by harboring extra metal ions and counterions for boosting the adsorption selectivity and uptake capacity simultaneously.